Effects of Scale on Multimodal Deixis: Evidence From Quiahije Chatino - Mesh, Kate; Cruz, Emiliana; van de Weijer, Joost; Burenhult, Niclas; Gullberg, Marianne (Frontiers in Psychology, 2021)
As humans interact in the world, they often orient one another's attention to objects through the use of spoken demonstrative expressions and head and/or hand movements to point to the objects. Although indicating behaviors have frequently been studied in lab settings, we know surprisingly little about how demonstratives and pointing are used to coordinate attention in large-scale space and in natural contexts. This study investigates how speakers of Quiahije Chatino, an indigenous language of Mexico, use demonstratives and pointing to give directions to named places in large-scale space across multiple scales (local activity, district, state). The results show that the use and coordination of demonstratives and pointing change as the scale of search space for the target grows. At larger scales, demonstratives and pointing are more likely to occur together, and the two signals appear to manage different aspects of the search for the target: demonstratives orient attention primarily to the gesturing body, while pointing provides cues for narrowing the search space. These findings underscore the distinct contributions of speech and gesture to the linguistic composite, while illustrating the dynamic nature of their interplay. Abstracts in Spanish and Quiahije Chatino are provided as appendices. Se incluyen como apéndices resúmenes en español y en el chatino de San Juan Quiahije. SonG ktyiC reC inH, ngyaqC skaE ktyiC noE ndaH sonB naF ngaJ noI ngyaqC loE ktyiC reC, ngyaqC ranF chaqE xlyaK qoE chaqF jnyaJ noA ndywiqA renqA KchinA KyqyaC.